2009
DOI: 10.4315/0362-028x-72.6.1342
|View full text |Cite
|
Sign up to set email alerts
|

Nonculturable Response of Animal Enteropathogens in the Agricultural Environment and Implications for Food Safety

Abstract: Concerns about animal enteropathogen contamination of fresh horticultural products have,increased worldwide and are mainly due to the ability of bacteria to survive under stress conditions in the agricultural environment and during raw-vegetable processing. This review challenges the idea that the viable but nonculturable phenomenon that has been proven to occur in plant-associated environments contributes to human pathogen survival and might be correlated with foodborne infection. Factors associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 110 publications
1
12
0
Order By: Relevance
“…The VBNC state is thought to be a transient physiological phase in which cells switch off activities typical for growing organisms but maintain a low level of metabolic activity without remaining culturable on routine microbiological media (26,31,39). There is compelling evidence that the nonculturable response occurs in different environmental and food matrices, but the significance of the passage into a dormancy stage and recovery is controversial (14).…”
mentioning
confidence: 99%
“…The VBNC state is thought to be a transient physiological phase in which cells switch off activities typical for growing organisms but maintain a low level of metabolic activity without remaining culturable on routine microbiological media (26,31,39). There is compelling evidence that the nonculturable response occurs in different environmental and food matrices, but the significance of the passage into a dormancy stage and recovery is controversial (14).…”
mentioning
confidence: 99%
“…10 3 CFU/g. Concerns regarding stressed cells and nonculturable response should be further investigated to confirm the inactivation effect of gaseous ozone treatment (Dinu et al, 2009). For viruses, it was reported that ozone damaged the protein capsid but the RNA remained intact after the treatment (Pascual et al, 2007;Zhang et al, 2011;Predmore et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The passing of pathogenic bacteria cells (eg Salmonella sp, Campylobacter jejuni, Vibrio vulnificus, Vibrio parahaemolyticus, Yersinia enterocolitica and Escherichia coli) into VBNC forms is particularly dangerous, as they remain active all the time. Additionally, they have higher virulence than the cells which are not influenced by the stressors [39,40].…”
Section: Microbiological Analyses Of Drinking Watermentioning
confidence: 99%
“…Consequently, classic methods for detection and qualitative determination of strains forming the biofilm may be insufficient. The presence of microbes in the VBNC state in a given environment can be detected with methods of cell viability determination, such as the ATP assay, and without using traditional agar plating techniques [39].…”
Section: Microbiological Analyses Of Drinking Watermentioning
confidence: 99%